HEGEMONI KEKUASAAN DALAM LIRIK LAGU RAP “PANOPTIKANUBIS” KARYA HOMICIDE - Yakobus M. Langkelang Niron; Karolus Budiman Jama (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
Lyrics in the flow of rap songs have a major role as a producer of meaning and aesthetics of a rap song. The concept of rap song lyrics has similarities with poetry and prose so that it can be said to be a literary text type. This study aims to examine the meaning comprehensively and described the forms of hegemony of power expressed in the lyrics of the rap song entitled